Germinal center B cells selectively oxidize fatty acids for energy while conducting minimal glycolysis - Weisel, Florian J.; Mullett, Steven J.; Elsner, Rebecca A.; Menk, Ashley V.; Trivedi, Nikita; Luo, Wei; Wikenheiser, Daniel; Hawse, William F.; Chikina, Maria; Smita, Shuchi; Conter, Laura J.; Joachim, Stephen M.; et al. (Nature Immunology, 2020)
Germinal center B cells (GCBCs) are critical for generating long-lived humoral immunity. How GCBCs meet the energetic challenge of rapid proliferation is poorly understood. Dividing lymphocytes typically rely on aerobic glycolysis over oxidative phosphorylation for energy. Here we report that GCBCs are exceptional among proliferating B and T cells, as they actively oxidize fatty acids (FAs) and conduct minimal glycolysis. In vitro, GCBCs had a very low glycolytic extracellular acidification rate but consumed oxygen in response to FAs. [13C6]-glucose feeding revealed that GCBCs generate significantly less phosphorylated glucose and little lactate. Further, GCBCs did not metabolize glucose into tricarboxylic acid (TCA) cycle intermediates. Conversely, [13C16]-palmitic acid labeling demonstrated that GCBCs generate most of their acetyl-CoA and acetylcarnitine from FAs. FA oxidation was functionally important, as drug-mediated and genetic dampening of FA oxidation resulted in a selective reduction of GCBCs. Hence, GCBCs appear to uncouple rapid proliferation from aerobic glycolysis.
CRIS-Team Scopus Importer:2020-03-06